Research on Relevant Dimensions of Tourism Experience of Intangible Cultural Heritage Lantern Festival: Integrating Generic Learning Outcomes With the Technology Acceptance Model - Li, Xin-Zhu; Chen, Chun-Ching; Kang, Xin; Kang, Jian (Frontiers in Psychology, 2022)
The Lantern Exhibition on the Lantern Festival is an important traditional festival in Taiwan. Visitors play an important role in the promotion and sustainable development of Intangible Cultural Heritage (ICH). In recent years, the involvement of digital technology in traditional lantern design and shows has contributed to the protection, inheritance, and promotion of ICH, there remains less research on using AR with Intangible cultural heritage Tourism. In this study, Augmented Reality (AR) is used for ICH lantern exhibition to discuss the learning experience in lantern tourism and the relationship between technology acceptance and satisfaction from the perspective of visitors, as well as evaluate what AR has on improving visitors’ awareness and learning experience. Then, primary variables of the Technology Acceptance Model (TAM) are combined with Generic learning outcomes (GLOs) to integrate ICH, education, and technology to expand TAM, building a new model to study ICH learning experience. A questionnaire and observation are used. Respondents are visitors participating in the AR lantern exhibition in Taiwan, which is designed by the author. There is a total of 200 questionnaires collected in the end. The result shows that Knowledge and Understanding (KU), Attitudes and Values (AV), Activity, Behavior, and Progression (PBP), Enjoyment, Inspiration, and Creativity (EIC) from GLOs have a positive effect on technology acceptance and Actual Use (AU). Therefore, visitors are satisfied with innovative and interesting technology learning experiences, enhancing learning interest and results. Besides, the interaction of AR system improves visitors learning motivation, which shows the combination of AR technology with ICH tourism helps improve cultural awareness.